2010
DOI: 10.1073/pnas.1011686107
|View full text |Cite|
|
Sign up to set email alerts
|

Structure-based development of a receptor activator of nuclear factor-κB ligand (RANKL) inhibitor peptide and molecular basis for osteopetrosis

Abstract: The receptor activator of nuclear factor-κB (RANK) and its ligand RANKL, which belong to the tumor necrosis factor (TNF) receptor-ligand family, mediate osteoclastogenesis. The crystal structure of the RANKL ectodomain (eRANKL) in complex with the RANK ectodomain (eRANK) combined with biochemical assays of RANK mutants indicated that three RANK loops (Loop1, Loop2, and Loop3) bind to the interface of a trimeric eRANKL. Loop3 is particularly notable in that it is structurally distinctive from other TNF-family r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 31 publications
4
59
0
2
Order By: Relevance
“…4C, 4D). Similarly, it has also been shown that mutation of RANK residue Asp 85 at site I did not significantly affect the RANKL binding and inhibition of osteoclast differentiation by soluble RANK (26). At site II, the general binding mode of an inserted loop from receptor into RANKL trimer is also conserved in the RANKL/OPG-CRD and RANKL/RANK complexes.…”
Section: Comparison With Rankl/rank Complexmentioning
confidence: 91%
See 2 more Smart Citations
“…4C, 4D). Similarly, it has also been shown that mutation of RANK residue Asp 85 at site I did not significantly affect the RANKL binding and inhibition of osteoclast differentiation by soluble RANK (26). At site II, the general binding mode of an inserted loop from receptor into RANKL trimer is also conserved in the RANKL/OPG-CRD and RANKL/RANK complexes.…”
Section: Comparison With Rankl/rank Complexmentioning
confidence: 91%
“…Mouse RANKL Lys 256 has interaction with RANK Lys 97 at the interface. Mutation of either Glu 126 or Lys 97 at RANK completely abrogated the RANKL binding and inhibition of osteoclast differentiation by soluble RANK (26). We also performed a GST pull-down experiment using human GST-RANKL and its mutants with human OPG-CRD or human RANK.…”
Section: Comparison With Rankl/rank Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…RANK is a type I transmembrane receptor belonging to the TNF receptor superfamily. The crystal structure of the extracellular domain of RANK has recently been described in the presence and absence of RANKL (Ta et al 2010). These studies showed tight binding between RANK and RANKL and illustrate how single base changes to the receptor-binding domain in RANKL drastically reduce interaction with RANKL and prevent osteoclast formation.…”
Section: Formation Of Mature Osteoclastsmentioning
confidence: 99%
“…The extracellular domain (ECD) of LTβR comprises four CRDs and is expected to have similar overall architecture to other multidomain TNFRSF members such as TNFR1. Crystal structures of several ligand-receptor complexes in this superfamily (15)(16)(17)(18)(19)(20)(21)(22)(23) revealed that receptors bind in a symmetrical Significance Cytokines are proteins that modulate the activity of target cells via activation of cell-surface receptors. The trimeric cytokines of the tumor necrosis factor superfamily typically signal by inducing homotrimerization of their cognate receptors.…”
mentioning
confidence: 99%